Pengaruh Pendidikan Kesehatan Metode Stratagem dengan Media Audiovisual terhadap Pengetahuan Kesehatan Reproduksi Remaja di SMP 14 Jember (The Effect of Health Education through Audiovisual Media Stratagem Method toward the Knowledge of Teenage Reproducti - Reza Riyady Pragita; Retno Purwandari; Lantin Sulistyorini (Pustaka Kesehatan, 2017)
Teenagers have experienced changes in biological, psychological and social aspects. Teenagersare lacking of the knowledge regarding reproductive health. The purpose of this research was toanalyze the effect of health education through audiovisual media stratagem method toward theknowledge of teenage reproductive health at SMPN 14 Jember. This research involved 15individuals who served as the experiment group, and 15 individuals who served as thecontrolgroup by using proportional stratified random sampling. The statistical test used wasWilcoxon and Mann Whitney. Results of the data is p value of 0.014 and 0.016 (α <0.05). Theconclusion of this research stated that there is a significant effect between health educationthrough audiovisual media stratagem method on the knowledge of teenagers in SMPN 14Jember regarding reproductive health and the variance in the effect of health education throughaudiovisual media stratagem method and conventional methods. Recommendations of thisresearch suggest that teenagers create reproductive health groups that play an active role in theprevention of teenagers’ reproductive health issues by using cooperative methods.Keywords: Teenagers, Health Education, Reproductive Health.